捕らわれの身になる求婚者 : フェロー語バラッド3作品をめぐって - 林, 邦彦; 1496; ハヤシ, クニヒコ; 9000402917141; HAYASHI, Kunihiko (尚美学園大学芸術情報学部・大学院芸術情報研究科, 2021)
論文 Articles デンマーク自治領のフェロー諸島で多数伝承されるフェロー語のバラッド作品群に、「男性が他国の権力者の娘との結婚を望み、求婚に出向くも、現地で捕らわれの身となる。求婚相手（権力者の娘）が自らの父（権力者）に求婚者の解放を嘆願するも認められず、求婚者の兄弟が救援に駆けつける」との物語を伝える作品が複数見受けられる。これらのうち、アーサー王伝説等に取材したバラッド・サイクル『ヘリントの息子ウィヴィント』（CCF108）を構成するサブ・バラッドの一つである『クヴィチルスプラング』と、このサイクルとは別の独立したバラッド『美丈夫フィンヌル』（CCF 26）の物語の類似はしばしば指摘されるが、本稿ではフェロー語バラッド作品で、これら二作品との物語の類似や影響関係についてはあまり指摘されない『コンスタンティノープルのハラルドシェルドゥル』（CCF 62）について、前出の二作品との内容上の比較を行い、この作品の位置づけや物語の由来をめぐる考察を試みたい。 Some of the Faroese ballads relate the story of a suitor who is imprisoned by the wooed maiden’s father（ the ruler of a certain district） and is later rescued by the wooer’s brother after the maiden’s father rejects her plea for his release such as Kvikilsprang ,one of the sub-ballads comprising the ballad-cycle Ívint Herintsson （CCF108）, which contains several Arthurian materials, and an independent ballad Finnur hin fríði（CCF26）. This article focuses on the Faroese ballad Haraldskjøldur á Miklagarði（CCF62）, a ballad which relates a similar type of story to the two aforementioned ballads but has not been so often studied in relation to them, and compares it with them in order to reveal the ballad’s position among the related works and the origin of its story. departmental bulletin paper